Toward the Development of a Sustainable Scientific Research Culture in Azerbaijan (2011–2015) - Aliyeva, Saida; Flanagan, Peter; Johnson, April; Strelow, Lisa (Frontiers in Public Health, 2016)
This review especially describes the dangerous pathogens research program in Azerbaijan (AJ) funded by the US Defense Threat Reduction Agency under the Cooperative Biological Engagement Program (CBEP) from 2011 through 2015. The objectives of the CBEP are to prevent the proliferation of biological weapons; to consolidate and secure collections of dangerous pathogens in central repositories; to strengthen biosafety and biosecurity of laboratory facilities; and to improve partner nations’ ability to detect, diagnose, report, and respond to outbreaks of disease caused by especially dangerous pathogens. One of the missions of the CBEP is therefore to increase the research skills and proficiency of partner country scientists. The program aims to fulfill this mission by sponsoring scientific research projects that exercise the modern diagnostic techniques available in the CBEP-engaged laboratories and the enhanced disease surveillance/control programs. To strengthen the local scientists’ ability to develop research ideas, write grant proposals, and conduct research independently, in-country CBEP integrating contractor personnel have mentored scientists across AJ and conducted workshops to address technical gaps. As a result of CBEP engagement, seven research projects developed and led by AJ scientists have been funded, and five projects are currently in various stages of implementation. The Defense Threat Reduction Agency has also sponsored AJ scientist participation at international scientific conferences to introduce and integrate them into the global scientific community. The efforts summarized in this review represent the first steps in an ongoing process that will ultimately provide AJ scientists with the skills and resources to plan and implement research projects of local and regional relevance.